2015
DOI: 10.1080/19313152.2014.977712
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Ideologies of Linguistic Purism: How Dual Language Teachers Make Sense of Everyday Translanguaging

Abstract: This article draws on qualitative data from two Spanish-English dual language elementary classrooms to explore how teachers in these classrooms made sense of the everyday practice of bilingualism. Methodologically, this study relied on participant observation, video recording, and semi-structured interviews. Conceptually, this article draws on the notion of translanguaging to describe how these teachers and their students moved fluidly across multiple languages and dialects in their everyday interactions. Draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(94 citation statements)
references
References 28 publications
4
80
0
7
Order By: Relevance
“…Students' cultural and linguistic resources, or their "funds of knowledge" from home communities (Moll et al, 1992), are used to support academic learning as ELLs develop new resources to be able to participate in new situations, bridging home and school and enhancing opportunities for students to learn (Valenzuela, 1999). Teachers can draw on ELLs' bilingual repertoires as supports for culture (Martinez, Hikida, & Durán, 2015), as ELLs use their bilingual resources in classrooms as resources without artificial linguistic boundaries (Gort & Sembiante, 2015).…”
Section: Principles Of a Language-based Approach To Content Instructionmentioning
confidence: 99%
“…Students' cultural and linguistic resources, or their "funds of knowledge" from home communities (Moll et al, 1992), are used to support academic learning as ELLs develop new resources to be able to participate in new situations, bridging home and school and enhancing opportunities for students to learn (Valenzuela, 1999). Teachers can draw on ELLs' bilingual repertoires as supports for culture (Martinez, Hikida, & Durán, 2015), as ELLs use their bilingual resources in classrooms as resources without artificial linguistic boundaries (Gort & Sembiante, 2015).…”
Section: Principles Of a Language-based Approach To Content Instructionmentioning
confidence: 99%
“…Arthur and Martin () also suggest that linguistic prestige, or how language relates to power, can shape classroom use of LOTEs. Martínez, Hikida, and Durán (), for example, found that despite teachers’ articulated ideologies about the importance of using both Spanish and English in elementary classrooms, their actual instructional practices encouraged a separation between languages. Similarly, Martínez‐Roldán's () use of activity theory highlights how classroom goals can “reinforce the hegemony of English” (p. 43) in activity systems.…”
Section: Learning Contexts and Lotesmentioning
confidence: 99%
“…Ideologies vary across populations, are fluid, and can even conflict within the individual. Ideologies can be articulated by an individual or embodied in that individual's activities, and there is an important relationship between the two (Martínez et al., ). For teachers, knowing why students use language is critical for informing how that language can be leveraged in instruction.…”
Section: Translanguaging: Practices and Ideologies In The Classroommentioning
confidence: 99%
“…First, we frame students' strategic use of multiple languages as translanguaging, or the practices associated with moving across languages and registers of speech to make meaning (O. García, ). Next, we explore these practices through elicited firsthand accounts of how teens use language and how their dispositions toward language, or language ideologies (Martínez, Hikida, & Durán, ), might influence this use. We then make pedagogical recommendations that build on students' strategic translanguaging to achieve goals.…”
mentioning
confidence: 99%